To solve this system of equations, we can use the method of substitution or elimination.
Let's first solve for x in terms of y from the second equation:
-x + 3y = 22
x = 3y - 22
Now substitute this value of x into the first equation:
5(3y - 22) - 4y = -44
15y - 110 - 4y = -44
11y = 66
y = 6
Now that we have found the value of y, we can substitute it back into the second equation to solve for x:
-x + 3(6) = 22
-x + 18 = 22
-x = 4
x = -4
Therefore, the solution to the system of equations is x = -4, y = 6.
solve the system of equations.
5x-4y=-44
-x+3y=22 (1 point)
1 answer